Upper gastrointestinal bleeding: Causes and patient outcomes - Almadi, Majid A. (Saudi J Gastroenterol, 2020)
BACKGROUND: Upper gastrointestinal bleeding (UGIB) remains a healthcare burden and is associated with considerable morbidity and mortality. We aim to describe the presentation, clinical, and laboratory characteristics of patients presenting with UGIB as well as important patient outcomes. METHODS: This is a retrospective study performed at a tertiary care university hospital in Riyadh. Electronic endoscopic reports of patients undergoing gastroscopies for the indication of UGIB from January 2006 to January 2015 were included. Demographic data, past medical conditions, medications used, symptoms on presentation, as well as the patients' hemodynamic status, laboratory investigations on presentations, the need for blood products, the need for admission to an intensive care unit, rebleeding, and in-hospital mortality rates were retrieved from medical records. RESULTS: Two hundred fifty-nine patients were included with a mean age of 57.1 years and males constituted 66.8% of the study cohort. At least one comorbidity was present in 88.2%, while 20.7% had a history of prior UGIB, 12.6% had a history of peptic ulcer disease, and 9.2% had known esophageal varices. A nonvariceal source represented 80.1% of the causes (95% CI: 75.4 to 85.3%), 15.5% required admission to the intensive care unit (ICU), the rebleeding rate was 8.9% (95% CI; 5.7% to 12.2%) while the in-hospital mortality was 4.4% (95% CI; 2.4% to 6.9%). The mean pre-endoscopic Rockall score was 2.6 (range: 0 to 5), while the total Rockall score was 4.4 (range: 1 to 9). There was no association between the pre-endoscopic Rockall score and rebleeding (3.0 vs. 2.5, P = 0.27) or need for ICU admission (3.2 vs. 2.4, P = 0.08), the total Rockall score and rebleeding (5.0 vs. 4.4, P = 0.58) or need for ICU admission (5.0 vs. 4.3, P = 0.36). CONCLUSION: Causes of UGIB in this patient population were predominantly nonvariceal and the rebleeding and mortality rates resembled those of other studies.